2010
DOI: 10.1002/chem.201000437
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Reverse Micelles Create Water with Super Hydrogen‐Bond‐Donor Capacity for Enzymatic Catalysis: Hydrolysis of 2‐Naphthyl Acetate by α‐Chymotrypsin

Abstract: Reverse micelles (RMs) are very good nanoreactors because they can create a unique microenvironment for carrying out a variety of chemical and biochemical reactions. The aim of the present work is to determine the influence of different RM interfaces on the hydrolysis of 2-naphthyl acetate (2-NA) by alpha-chymotrypsin (alpha-CT). The reaction was studied in water/benzyl-n-hexadecyldimethylammonium chloride (BHDC)/benzene RMs and, its efficiency compared with that observed in pure water and in sodium 1,4-bis-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
101
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 45 publications
0
101
0
Order By: Relevance
“…In this way, recently we have shown that the interfacial water properties can be very different depending on the charge of the surfactant polar head group [65,66]. Specifically, we have found different behavior of the fluorescent cationic hemicyanine trans-4-[4-(dimethylamino)-styryl]-N-methylpyridinium iodide, depending on whether the probe is solvated by the water in AOT or in BHDC reversed micellar systems.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this way, recently we have shown that the interfacial water properties can be very different depending on the charge of the surfactant polar head group [65,66]. Specifically, we have found different behavior of the fluorescent cationic hemicyanine trans-4-[4-(dimethylamino)-styryl]-N-methylpyridinium iodide, depending on whether the probe is solvated by the water in AOT or in BHDC reversed micellar systems.…”
Section: Introductionmentioning
confidence: 92%
“…The results suggested that the water molecules sequestrated inside AOT and BHDC reversed micellar systems show important differences in its properties because they interact in different form with the surfactants polar head [65]. Also, quite recently, we have investigated the influence of different reversed micellar interfaces on the hydrolysis of 2-naphthyl acetate by achymotrypsin [66]. This reaction was studied in benzene/BHDC/ water RMs, and its efficiency was compared with that observed in pure water and in AOT RMs.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, the water at the cationic RMs interfaces seems to have enhanced hydrogen-bonddonor capability. [27,28,38] Phenols have been used as molecular probes to determine binding constants at the AOT RMs interface [39,40] or to measure pK a values upon confinement. [41][42][43] The behavior of different phenols in RMs were investigated by Magid et al [40] They calculated the binding constants for a series of phenols to AOT RMs and found that the binding process depended mainly on the hydrogen-bonding ability of the phenols to form hydrogen bonds with the AOT polar head groups.…”
Section: Introductionmentioning
confidence: 99%
“…Also, very recently we found that 2-naphthol converted into 2-naphtholate in BHDC RMs, but not in AOT RMs. [28] We explained this fact by considering differences in the interfacial water properties. Water molecules trapped inside the AOT RMs had enhanced electron-donor abilities than those of bulk water.…”
mentioning
confidence: 99%